The acute metabolic responses during crossfit-based and tabata-based workout protocol among healthy individuals - Ahmad Shairazi Abdul Fatah (Tanjong Malim, 2021)
The acute metabolic responses during crossfit-based and tabata-based workout protocol among healthy individuals by Ahmad Shairazi Abdul Fatah